Poverty Reduction Strategy Through Food Security During The Covid 19 Pandemic In Banjar City - Nada Ulfah Avionita; Ida Widianingsih; Ramadhan Pancasilawan (Universitas Padjadjaran, 2022)
Poverty is a condition of economic inability to meet the standard of living of the average community in an area. This inability condition is characterized by the low ability of income to meet basic needs in the form of food, clothing, and housing. This low income ability will also have an impact on reducing the ability to meet average living standards such as public health standards and education standards (Wini, 2010:21). The city of Banjar has the potential for agricultural natural resources to be developed which is supported by the population based on data from the Central Statistics Agency (BPS), the population of Banjar City who is in the poverty line is 5.70 percent, meaning that the agricultural sector has not been able to save the people of Banjar City in alleviating poverty. The city of Banjar, like other regions in Indonesia, must be able to help make this happen by prioritizing its food security, that national food security is the main key in facing the next crisis period after the corona pandemic outbreak ends. All countries in the world in the recovery period will begin to build their own food strength by increasing agricultural production.